Instructional Strategies, Personality Types and the Outcome of Junior High School Students on Learning Bahasa Indonesia - Mularsih, Heni (Makara Human Behavior Studies in Asia, 2010)
The objective of the research is to study the effect of the instructional strategies (cooperative and individual learning) and personality types (extrovert and introvert) on the outcome of students on learning Indonesian language. The research employed the experimental method with 2 x 2 factorial design on a sample of 48 students, conducted at the secondary school in Tangerang City. The result of the research shows that: (1) the outcome of students learning following the instruction with cooperative strategy are higher than those following individual instruction, (2) there are no significant differences of learning outcome between the students having extrovert type and introvert type of personality, (3) there is a significant interaction effect between the instructional strategy and the personality type on the secondary school outcome of the students learning Indonesian language, (4) the outcome of extrovert type students learning, following the instruction with cooperative strategy are higher than those following individual instruction, (5) the outcome of introvert type students learning, following the instruction with individual strategy are higher than those following cooperative instruction. In conclusion, the instructional strategy can increase the outcome of students learning Indonesian language by considering the students’ personality type.